Efektivitas Pengelolaan Administrasi Dalam Meningkatkan Pelayanan Pada Badan Pelaksana Penyuluhan Pertanian Perikanan dan Kehutanan (BP4K) - Mahabu, Suleman (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2024)
The aim of this research is to find out: How effective is administrative management in improving services at the Pohuwato Regency Agriculture, Fisheries and Forestry Extension Agency (BP4K); What factors hinder the effectiveness of administrative management in improving services at the Pohuwato Regency Agriculture, Fisheries and Forestry Extension Agency (BP4K). In this research, researchers used primary data through interviews with officials at the Pohuwato Regency Agricultural, Fishery and Forestry Extension Implementing Agency (BP4K), where interviews were conducted from May 2016 to August 2016. The results of this research show that the effectiveness of administrative management in improving services at the implementing agency Pohuwato Regency Agriculture, Fisheries and Forestry Extension (BP4K) has not been implemented well. This is shown by the existence of obstacles which generally come from employees due to minimal education, skills and facilities available in carrying out work. It is recommended to the Implementing Agency for Agriculture, Fisheries and Forestry Extension (BP4K) of Pohuwato Regency to increase human resources and infrastructure so that the services provided by employees can satisfy interested parties.